2015
DOI: 10.5171/2015.563217
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Erythrocytes and Lipid Profiles of Blood Plasma

Abstract: The study was carried out to evaluate the influence of lipid blood plasma in patients with stable angina on some rheological properties of the erythrocytes. Our study revealed that atherogenic lipids increased erythrocyte's aggregation, but level of high density lipoproteins has no affect on the aggregation. Erythrocyte deformability of red blood cells was not associated with the plasma lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…This study revealed that atherogenic lipids increased erythrocyte's aggregation, but not erythrocyte deformability. (17) The increase in MCV was significant in diabetic males and insignificant in diabetic females (9) and there was correlation between HbA1c and MCHC in diabetic subjects (18). In the present study, we found that only MCV was correlated significantly with FPG, PPG, HbA1c and HOMA-IR.…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…This study revealed that atherogenic lipids increased erythrocyte's aggregation, but not erythrocyte deformability. (17) The increase in MCV was significant in diabetic males and insignificant in diabetic females (9) and there was correlation between HbA1c and MCHC in diabetic subjects (18). In the present study, we found that only MCV was correlated significantly with FPG, PPG, HbA1c and HOMA-IR.…”
Section: Laboratory Assaysmentioning
confidence: 99%